Pelatihan Kewirausahaan Sosial untuk Warga Binaan Rumah Tahanan Negara Kelas I Pondok Bambu - Chrisbiantoro, Chrisbiantoro; Rosyidi, Ahmad Fanani; Aziz, Jakfar Rafki Abdul (Jurnal Pengabdian Masyarakat Singa Podium (JPMSIPO), 2024)
The empowerment of assisted citizens in the Detention Center is a very important component in building a sustainable chain of empowerment up to the Correctional Institution level and can later continue to the Correctional Center level, as the last gate that debriefs fostered residents to return to the community. In addition to the government, academics, as a component of the nation's children, must take an important role in this program through community service so that the presence of academics will be greatly felt by the community, especially fostered citizens. Of course, academics cannot run alone; they must synergize with other components, both social activists and business people who can help fund community service programs. So that the synergy will produce an excellent portfolio, especially in the field of empowerment of prison-assisted citizens. Through the social entrepreneurship training program, it is hoped that it can provide provisions to the assisted residents of the Pondok Bambu Class 1 Detention Center and also provide wider inspiration so that all parties can take a role so that the sustainability of empowerment can continue to be carried out.